A State-of-the-Art Review of New and Emerging Therapies for the Treatment of IBD. Issue 5 (15th November 2018) - Chudy-Onwugaje, Kenechukwu O; Christian, Kaci E; Farraye, Francis A; Cross, Raymond K
Abstract: Over the last 2 decades, novel therapies targeting several immune pathways have been developed for the treatment of patients with inflammatory bowel disease (IBD). Although anti–tumor necrosis factor (anti-TNF) agents remain the firstline treatment for moderate to severe Crohn's disease and ulcerative colitis, many patients will require alternative agents, due to nonresponse, loss of response, or intolerance of anti-TNFs. Furthermore, patients may request newer therapies due to improved safety profiles or improved administration (ie, less frequent injection, oral therapy). This review will focus on new and emerging therapies for the treatment of IBD, with a special focus on their adverse effects. Although many of the agents included in this paper have been approved for use in IBD, a few are still in development but have been shown to be effective in phase II clinical trials. Video Abstract: